The meaning of the border in existentialism (ontological point of view) - Demirtshyan, Movses (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
The article examines the different meanings of the concept of border in the works of a number of representatives of existentialist philosophy. The authors who have discussed ontological issues related to the border are in the center of attention: A. Camus, K. Jaspers, J.-P. Sartre, H.-G. Gadamer. The interpretations of the border in existentialist philosophy, although based on the tradition of classical philosophy, in which the epistemological aspect of the border was discussed mostly, nevertheless add a new approach, according to which the border is an important feature of human existence that defines our existence as a situation, project and communication. The physical, social and mental boundaries of human existence outline our existence, makes it from abstract-contemplative to concrete and tangible. Time and space, age and social status, legal, moral norms and other limitations turn our lives into a shift of situations in which we are constantly stand. In existentialism, human existence is connected with those situations in which man has to make maximum intellectual, emotional and volitional efforts to orient himself. As these situations are created due to borders, our existence itself becomes a border phenomenon. It is especially manifested in borderline situations, which force a person to reconsider his ideas about his own existence, life and other people. In existentialism, the border is also interpreted as a project, which symbolizes the extent to which other people interfere in the privacy of the future. This interpretation can be found in Camus's teaching on revolt.Another view of border ontology is based on the interpretation of the border as communication. Through communication a person goes beyond his narrow personal boundaries, expands his limits of consciousness and understanding, notices that he has a lot in common with other people, generally overcomes the danger of being summed up in the "I", loses the connection with other people. Communication is vital in the sense that it delineates the boundaries of human coexistence.
Keywords: border; existentialism; size; existence; communication; borderline situation; freedom